Preliminary agency statement of natural resource management priorities in Western Australia - Western Australia; Western Australia. Department of Agriculture; Western Australia. Department of Environment (East Perth, W.A. : Dept. of Environment, 2003)
The report covers all natural resources as assets in a "whole of government" approach, by the natural resource management agencies: Dept. of Agriculture, Dept. of Conservation and Land Management, Dept. of Environment and Dept. of Fisheries.
Cover title.
Includes bibliographical references.
Keywords: Land use -- Government policy -- Western Australia; Conservation of natural resources -- Western Australia -- Planning; Conservation of natural resources -- Government policy -- Western Australia; Biological diversity conservation -- Western Australia